Occurrence of extended spectrum Beta-Lactamase producing escherichia coli in dairy cattle, farm environment and milk - Kamaruzzaman, Emelia Aini (2015)
Emerging of newer groups of antibiotic resistant bacteria is widely reported as a result of the persistent use of antibiotic either for therapeutic or prophylactic purposes. Extended-Spectrum Beta Lactamase (ESBL) is an enzyme produced by gram-negative bacteria which developed resistance to beta lactam antibiotics ranging from penicillin to third and fourth generation cephalosporin; however its activity is inhibited by clavulanic acid. Due to less therapeutic options,human infections caused by ESBL-producing organisms are associated with treatment failure, increased morbidity, increase in length of hospital stay and therapeutic cost, and mortality. Three objectives in the study were first, to determine the occurrence of Extended Spectrum Beta-Lactamase producing E. coli (ESBL-producing E. coli) in dairy cattle, farm environment and milk; secondly to determine the risk factors associated with the occurrence, and thirdly to determine the antibiotic resistance patterns of the ESBL-producing E. coli. Samples collected comprised fecal samples (n=229), farm environment (n=77) including stall floors, feed and water trough, house flies (Musca domestica), feed, drinking water and source of drinking water; and milk (n=71) from 10 dairy farms located within Selangor and Negeri Sembilan. Phenotypic detection of ESBL-producing E. coli was carried out. The overall occurrence of ESBL-producing E. coli was 4.8%. There was a significant difference in the occurrence of ESBL-producing E. coli (p=0.00) in all three sample groups. The highest occurrence of ESBLproducing E. coli was in milk (66.7%) followed by farm environment (27.8%) and cattle (5.5%). Molecular detection of four ESBL genes namely TEM, SHV, CTX-M and OXA was done using multiplex Polymerase Chain Reaction (m-PCR) method. The CTX-M gene was predominantly detected in 12 out of 18 isolates (66.7%). The risk factors associated with the occurrence of ESBL-producing E.coli in dairy cattle, farm environment and milk were investigated through questionnaires seeking information related to farm management and husbandry practices, records on animal health including antibiotic usage by the farm owners. Two factors found to be statistically significant (p<0.05) were “presence of other animal in the farm compound” (χ2 = 5.173, p=0.023) and “previous history of disease outbreak” (χ2 = 3.869, p=0.049). Beef cattle, goats, poultry species including native chickens, duck and geese as well as companion animals such as cats and dogs have been reported to be possible sources of ESBL-producing E. coli in the farms. Antibiotic susceptibility test was conducted using disk diffusion method against 12 antibiotics belonging to six classes which included beta-lactams, chloramphenicol, macrolides, aminoglycoside, quinolones and sulfonamides. Sixteen (88.9%) of 18 ESBL-producing E. coli isolates showed resistance to all six beta-lactam antibiotics, with only one isolate (5.6%) from the drinking water was found to be resistant to all 12 antibiotics. All isolates (100%) were found to be resistant against cefotaxime, ceftriaxone and aztreonam. ESBL-producing E. coli showed highest susceptibility to trimethoprim-sulphamethoxazole (88.9%) followed by gentamicin and ciprofloxacin (83.3% each). Ten isolates (55.6%) were found to be multi-drug resistant, that is, resistant to three or more antibiotic classes. It is crucial to determine the resistance patterns of ESBL-producing E. coli isolates for the purpose of antibiotic selection for treatment options. In conclusion, the occurrence of ESBL-producing E. coli in dairy cattle,farm environment and milk is of public health significance, although it was low. The presence of antibiotic-resistant bacteria may possibly be due to imprudent use of antibiotic, or acquire from the environment. Such imprudent use of antibiotics in animal production may contribute to the persistence of zoonotic resistant organisms in food producing animals as well as in the environments and food products, hence pose serious risks to human health.